Suicide attempts by exogenous intoxication among female adolescents treated at a reference hospital in the city of Recife-PE, Brazil - Juliana Lourenço de Araújo Veras; Cintia Regina Tornisiello Katz (Associação Brasileira de Enfermagem, 2011)
This study aimed to assess cases of self-inflicted poisoning among adolescents reported by the Toxicological Care Center of a reference hospital in Recife-PE, Brazil. The data were collected between March and May 2010 from hospital charts and structured interviews with the participants and parents/guardians. Among the 25 cases of attempted suicide registered in the period, 21 were female adolescents, who made up the sample of the present study. The adolescents were between 13 and 19 years of age. Pesticides were the most frequent toxic agent used (61.9%). The results of the present study underscore the importance of studying suicide in this population, with a focus on family relations, in order to lay the foundation for the development of prevention and treatment programs for this vulnerable group.